Innentitelbild: Darobactine mit Überlegener Antibiotischer Aktivität Generiert durch Strukturgeleitetes Kryo‐EM‐Biosynthese‐Design (Angew. Chem. 2/2023). (14th December 2022) - Seyfert, Carsten E.; Porten, Christoph; Yuan, Biao; Deckarm, Selina; Panter, Fabian; Bader, Chantal D.; Coetzee, Janetta; Deschner, Felix; Tehrani, Kamaleddin H. M. E.; Higgins, Paul G.; Seifert, Harald; Marlovits, Thomas C.; et al.
Abstract : Darobactins bind to the novel antibiotic target BamA in the outer membrane BAM‐complex of Gram‐negative pathogens. The renewal of the outer membrane proteins is prevented and bacteria are lysed. The new derivative D22 was created through cryo‐EM structure‐ and activity‐guided biosynthetic engineering as described by Thomas C. Marlovits, Jennifer Herrmann, Rolf Müller et al. in their Research Article (e202214094), and showed superior potency against multidrug‐resistant clinical isolates, for which most antibiotics on the market are no longer effective.